2017
DOI: 10.1159/000465530
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-6 and Hepcidin Levels during Hormone-Deplete and Hormone-Replete Phases of an Oral Contraceptive Cycle: A Pilot Study

Abstract: Background: In the past, elevated estradiol levels were reported to downregulate the iron regulatory hormone hepcidin, thereby potentially improving iron metabolism. As estrogen plays a role in regulating the menstrual cycle and can influence the cytokine interleukin-6 (IL-6; a hepcidin up-regulator), this investigation examined the effects of estradiol supplementation achieved by the use of a monophasic oral contraceptive pill (OCP) on IL-6, hepcidin levels and iron status during the hormone-deplete versus ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(28 citation statements)
references
References 25 publications
11
17
0
Order By: Relevance
“…Earlier studies on human OC users reported no differences between OC phases for either hepcidin or IL‐6, either when at rest 14,24 or after performing a running exercise 14 . While the present results are in agreement with this, the latter authors' arguments indicate a supposed increase in estradiol concentration during the active pill phase had no effect on the above variables.…”
Section: Discussionsupporting
confidence: 88%
“…Earlier studies on human OC users reported no differences between OC phases for either hepcidin or IL‐6, either when at rest 14,24 or after performing a running exercise 14 . While the present results are in agreement with this, the latter authors' arguments indicate a supposed increase in estradiol concentration during the active pill phase had no effect on the above variables.…”
Section: Discussionsupporting
confidence: 88%
“…It may suggest that exercise induced increases in IL-6 are robust to exogenous estradiol and progesterone from OC, and therefore the subsequent normal and similar hepcidin response for both trials. In the same line, this response to exercise has been reported to be similar in IL-6 and hepcidin levels than the levels obtained during rest period for premenopausal women using monophasic OC (Sim et al, 2017), suggesting that OC do not affect basal IL-6 and hepcidin levels and may be linked to the lower dosage of estradiol delivered from the OC.…”
Section: The Influence Of Oral Contraceptives On Iron Parameterssupporting
confidence: 57%
“…Subjects attended at the laboratory at 07:00 am the test day, in order to minimize any potential diurnal effects on serum hepcidin and iron parameters levels (Kroot et al, 2010;Sim et al, 2017). The participants had breakfast 2 hours before arriving at the laboratory and abstained from alcohol, caffeine, and exercise for 24 hours before each test.…”
Section: Experimental Protocolmentioning
confidence: 99%
“…Similarly, the first study investigating the post-exercise IL-6 and hepcidin response, reported similar results for serum IL-6 and hepcidin for both hormone-deplete and hormone-replete phases of a monophasic OC cycle 64 . These results indicated that exercise performed during the different phases of a monophasic OC cycle does not alter exercise induced IL-6 or hepcidin production and it may be linked to the lower dosage of estradiol delivered from the OC 65 .…”
Section: Exogenous Hormones Influence On Iron Metabolismmentioning
confidence: 87%